ANALISIS ADOPSI PENERIMAAN TEKNOLOGI INFORMASI OLEH USAHA MIKRO, KECIL, DAN MENENGAH DI KECAMATAN PANTI KABUPATEN JEMBER - Ira Puspitadewi Samsuryaningrum; Jekti Rahayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study examines the effect of perceived usefulness and perceived ease of use on behavioral intention to use and actual use of information technology in Micro, Small, and Medium Enterprises (MSMEs). The sample of this study consisted of 40 respondents as the owners of MSMEs in Panti District, Jember Regency, which was taken by accidental sampling technique. SEM analysis was used to analyze research data. The results showed that perceived usefulness and perceived ease of use have significant effects on behavioral intention to use information technology. Perceived usefulness and perceived ease of use significantly affect the actual use of information technology. Results also showed that behavioral intention to use has a significant effect on the actual use of information technology. However, perceived usefulness through behavioral intention to use and perceived ease of use through behavioral intention to use did not significantly affect the actual use of information technology at MSME in Panti District, Jember Regency. Keywords: actual use, behavioral intention to use, e-commerce, perceived ease of use, perceived usefulness